Nesting aggregation as a Determinant of Brood Parasitism in Mason Bees (Osmia spp.) - Groulx, Adam (Université d'Ottawa / University of Ottawa, 2016)
Identifying forces that affect population dynamics can allow us to better understand the distribution and abundance of animals. Both top-down and bottom-up factors can significantly influence animal populations. Mason bees (members of the genus Osmia; Hymenoptera: Megachilidae) are important pollinators for agricultural systems and are vulnerable to exploitation by brood parasites, such as kleptoparasitic wasps. High levels of nesting density have the potential to increase rates of brood parasitism by attracting larger numbers of parasites to areas with aggregations of nests. I conducted a field study in subalpine meadows at the Rocky Mountain Biological Laboratory in Colorado, USA, to assess whether mason bees suffer increased brood parasitism as the size of nesting aggregations increases. Mason bees were allowed to nest in artificial nest boxes and establish natural variations in numbers of nesting individuals within nest boxes. Nest cells constructed by bees were then checked for the presence of kleptoparasite larvae shortly after they were completed. Overall, nest cells constructed in blocks containing multiple active bees were significantly more likely to be oviposited in by brood parasites compared to cells constructed in blocks with fewer active nesting bees. This suggests that gathering in large aggregations for nesting can negatively affect populations of mason bees, given the high levels of brood parasitism observed in areas of high nesting density. In addition, the last nest cell in mason bee nests was significantly more likely to be parasitized than inner cells, suggesting bees may be abandoning nests that are parasitized, representing a potential defensive response of bees to brood parasitism. These results have implications for the management of mason bees as agricultural pollinators, as cultivating them in large groups could reduce their survival.
Keywords: Parasitism; Mason Bees; Interspecies Interactions; Ecology; Pollinators